2009
DOI: 10.1038/sj.bjc.6605428
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C8 and CYP2C9 polymorphisms in relation to tumour characteristics and early breast cancer related events among 652 breast cancer patients

Abstract: BACKGROUND: CYP2C8/9 polymorphisms may influence breast cancer-free survival after diagnosis due to their role in the metabolism of tamoxifen, paclitaxel, and other chemotherapy. cytochrome P450 (CYP)2C8/9 metabolise arachidonic acid to epoxyeicosatrienoic acids, which enhance migration and invasion in vitro and promote angiogenesis in vivo. We aimed to investigate the frequency of CYP2C8/9 polymorphisms in relation to breast tumour characteristics and disease-free survival. METHODS: A prospective series of 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…It is therefore plausible that tamoxifen response is influenced by the CYP1A2*1F genotype and coffee intake and that any effect of coffee may be dependent on the CYP1A2*1F genotype. Similarly, CYP2C8*3 genotypes have previously been shown to be associated with an increased risk for early events in a subset of tamoxifen-treated patients from the present cohort [21]. Tamoxifen response may therefore also be influenced by CYP2C8 genotype and coffee intake.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is therefore plausible that tamoxifen response is influenced by the CYP1A2*1F genotype and coffee intake and that any effect of coffee may be dependent on the CYP1A2*1F genotype. Similarly, CYP2C8*3 genotypes have previously been shown to be associated with an increased risk for early events in a subset of tamoxifen-treated patients from the present cohort [21]. Tamoxifen response may therefore also be influenced by CYP2C8 genotype and coffee intake.…”
Section: Introductionsupporting
confidence: 54%
“…CYP2C8/9 also contributes to the metabolism of caffeine [17] and tamoxifen [16]. CYP2C8*3 genotypes, which may influence CYP2C8 enzyme metabolic activity [38], have previously been associated with a higher risk for early breast cancer events in tamoxifentreated patients, in a subset of the present cohort [21]. Intake of caffeinated coffee may thus result in increased activation of tamoxifen via CYP1A2 or CYP2C8/9, a hypothesis consistent with our finding of fewer early events in tamoxifen-treated patients with ER+ tumors and moderate to high coffee consumption.…”
Section: Discussionmentioning
confidence: 67%
“…The relationship between breast cancer and the CYP gene family was recently reported, including CYP1B1 (Economopoulos and Sergentanis, 2010;Ozbek et al, 2010), CYP2J2 (Jiang et al, 2007(Jiang et al, , 2009), CYP2D6 (Stingl et al, 2010;González-Tejera et al, 2010;Thompson et al, 2011), CYP2C8 (Knüpfer et al, 2004;Dixit, et al, 2007;Jernström et al, 2009), CYP2C9 (Ekhart et al, 2008;Jernström et al, 2009) and CYP2C19 (Justenhoven et al, 2009;Ruiter et al, 2010;Goetz and Suman, 2010). Several studies have reported different conclusions for the relationship with CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…After a written informed consent was signed, a questionnaire regarding lifestyle, reproductive factors, and medications was completed (10). Blood samples were taken and body measurements, including breast volume, were recorded by a research nurse.…”
Section: Introductionmentioning
confidence: 99%